Research on the Influence of Train Speed Change on the EMI of Pantograph-Catenary Arc to Main Navigation Stations - Yutao Tang; Feng Zhu; Yingying Chen (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The electromagnetic interference (EMI) of the pantograph-catenary arc (PCA) to the main navigation stations will be affected when the speed of the high-speed train is changed. In order to study the influence of the speed change, we measured and analyzed the electric field intensity of the PCA generated at common and neutral section of power supply line at different train speeds. The frequency range in this study is the frequency of the main navigation stations (108 336 MHz). Both theoretical and experimental results show that PCA radiation increases with the increase of train speed. Besides, we calculated the maximum train speed without interfering the navigation signal. This work is useful for estimating EMI of the PCA at different train speeds and mitigating the interference to the navigation station near the highspeed railway by proposing corresponding speed limits.